Bonnie MANN y Martina FERRARI (Eds.): “On ne naît pas femme: on le devient”. The life of a Sentence. New York: Oxford University Press, 2017, 354 pp. - Bąk, Agata Joanna (Investigaciones Fenomenológicas, 2021)
-